Mapping of recreation suitability in the Belgrad Forest Stands - Caglayan, Inci; Yesil, Ahmet; Cieszewski, Chris; Gul, Fatmagul Kilic; Kabak, Ozgur (ELSEVIER SCI LTD, 2020)
Istanbul is a fast-growing city with a more than 15 million population and limited possibilities of recreational opportunities within its perimeter. The Belgrad Forest, one of the largest forests in Istanbul, currently have only 3.18% of the area designated for recreation. The aim of this research is to assess and map of recreation area (RA) suitabilities in Belgrad Forest stands to enhance forest planning. By this way, the recreation potential of Belgrad Forest will be revealed for meeting the needs of Istanbul residents. We consider nine main criteria for determining the recreation suitability of forest stands (n = 1118). We use the Analytic Hierarchy Process approach to find the importance weights of criteria and sub-criteria as well as total suitability scores of the stands. Finally, we sort all the stands according to their suitability scores and assign them to three classes of recreational suitability: High, Moderate, and Low. Results suggest that the high suitability potential RAs in the Belgrad Forest constitute 8.25% of the total area. Therefore, there is an opportunity to extend the forest recreational uses in this area to at least 8.25%, which would be beneficial to the residents of Istanbul within an environment of expansive urbanization.
Keywords: MCDM; GIS; Analytic hierarchy process; Recreation suitability; Scenic beauty; Forest stands; CULTURAL ECOSYSTEM SERVICES; VISUAL QUALITY; DECISION; HOTSPOTS; IMPROVE; Geography